The Impact of Suseno Apriadi YouTube Channel on Student Engagement in DKV Students First Semester - Apriadi, Suseno; Nurlaila, Isnaeni Yasmin (Fakultas Komputer Dan Desain, 2026)
Abstract. The development of digital technology has introduced interactive alternative learning media, including YouTube. This study aims to explore the impact of the Suseno Apriadi YouTube channel on student engagement among first-semester Visual Communication Design (DKV) students. A qualitative descriptive approach was employed to gain an in-depth understanding of students’ learning experiences through observations, semi-structured interviews, and documentation of student works inspired by the channel’s content. The findings indicate that videos presented in a visually appealing, informative, and academically relevant manner significantly enhance student engagement across three dimensions: cognitive, emotional, and behavioral. Students not only grasp design concepts more easily but are also motivated to apply them in creative practice, improving learning motivation and developing visual aesthetic sensitivity. These results suggest that audiovisual media, particularly the Suseno Apriadi YouTube channel, can serve as an effective learning tool that integrates theory, practice, and aesthetic experience, thereby strengthening the quality of design education in the digital era. Keywords: YouTube, student engagement, Visual Communication Design, audiovisual learning, visual aesthetics.